Zn-fortified cereal grains in field-grown barley by enhanced root cytokinin breakdown - Ramireddy, Eswarayya; Galuszka, Petr; Schmülling, Thomas (Plant signaling & behavior, 2018)
Zinc (Zn) is an essential element in human nutrition. The concentration of Zn in cereals, which is a staple food in developing countries, is often too low thus contributing to Zn malnutrition in nearly two billion people worldwide. We have reported recently that transgenic barley plants expressing a cytokinin-degrading CYTOKININ OXIDASE/DEHYDROGENASE (CKX) gene in their roots form a larger root system and accumulate a higher concentration of Zn in their grains when grown under greenhouse conditions. Here, we have tested this trait under field conditions. Four independent pEPP:CKX lines accumulated an up to 30% higher Zn concentration in their grains as compared to the untransformed control suggesting that this is a stable trait. The increased Zn concentration exceeded the limit set by the HarvestPlus program for wheat. We, therefore, propose that root enhancement achieved by increased degradation of cytokinin in roots can be a sustainable strategy to combat malnutrition caused by Zn deficiency.
Keywords: Cytokinins; cytokininy; Zinc; cereals; Plants, Genetically Modified; root system architecture; biofortification; zinc; Plant Roots; Hordeum; rostlinné proteiny; kořeny rostlin; ječmen (rod); Hordeum vulgare; Barley; geneticky modifikované rostliny; Oxidoreductases; Plant Proteins; cytokinin oxidase/dehydrogenase; Edible Grain; zinek; cytokinin; jedlá semena; oxidoreduktasy